To reflect a function over the x-axis, you have to change the sign of the function, you can express this as:
![g(x)=-f(x)](https://img.qammunity.org/2023/formulas/mathematics/college/rweloub6zparwm3a4sol7tghag7j0y7s7f.png)
We know that the function f(x) has the following formula
![f(x)=3((1)/(2))^x](https://img.qammunity.org/2023/formulas/mathematics/college/1cwj66uxm1ygkbj7p6vg5htygv8v6e95ns.png)
Then, after the reflection over the x-axis, the function will have the following shape:
![\begin{gathered} g(x)=-f(x) \\ g(x)=-3((1)/(2))^x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/13vb807th0kxagq2h4hql4v4oh5w1zw4o5.png)
The correct option is the second one g(x)=-3(1/2)^x